Seminar “Architecture, Photography and Preservation Ofcities” pada Peserta The English Access Microscholarship Program (Access) Vitka Learning Center (VLC) - Muhammad Adi Sukma Nalendra; Dimas Akmarul Putera; Ria Sapitri; Dany Kurnia Gunawan; Zhilla Zhalila Qurrata A’yun; Tommy Andrea Gunawan; Jihan Nur Annisa (LPPM ITEBA, 2026)
Batam City is undergoing rapid urban development, which poses challenges to the preservation of architecture and the urban environment, while young people’s awareness of the historical and cultural value of city buildings remains low. This community service activity aimed to improve the understanding of participants of The English Access Microscholarship Program (ACCESS) at Vitka Learning Center (VLC) regarding the relationship between architecture, photography, and city preservation, while integrating it with learning to write descriptive texts in English. The methods used were community education through a seminar, basic photo-essay training, and field photography practice followed by narrative composition. Data were collected through observation, activity documentation, assessment of all participant works by two raters using a four-aspect rubric on a 1–4 scale, and a retrospective post-then-pre questionnaire completed by all 20 participants and analysed using the Wilcoxon signed-rank test. The seminar was held on 21 April 2025 at ACCESS VLC Batam and was attended by 20 participants. Rubric assessment of 20 works yielded a mean of 3.24 out of 4.00 (SD = 0.30), with 25% rated very good and 75% rated good. Relevance to the preservation theme scored highest (3.27), while narrative coherence of the photo sequence scored lowest (3.17). Self-rated scores rose from 1.79 to 4.21 on a 5-point scale (W = 0; z = −3.92; p < .001; r = 0.88), although these figures should be read as participant perception given the risk of inflation bias. Comparing both instruments revealed a divergence: the aspect participants perceived as most improved scored lowest in the work assessment. The output was participants’ photo-essay works that can be developed into a photo-essay book as a public education medium.